Attainment of the Right Theory; A Window to the Justifiability of judges' Supervision on Ordinary Laws - Amirhossein Alizadeh; Ghasem Alizadeh (پژوهشهای حقوقی)
Judge’s Fundamental judicial supervision on ordinary laws is one of the most important issues in the last decade. The problem is that the judge, in the position of hearing the case and invoking the rule of law, which may have a dual source in the constitution and the ordinary, can act as the basic supervisor of the ordinary law and set it aside? The new viewpoint is based on the theory of the attainment of the right and jurisdiction of the Judiciary. According to this view, the patterns of fundamental rules are based on the generality and foundations of the legal system and derive from all the effective norms affecting it and protecting the fundamental rights of individuals, and the judge as a selector person, due to the sources of right, selects the justice verified rule and settles the lawsuit. In this view, the legal rules are subject to the basic duty of the Judiciary in such a way that the judge refuses to enforce them in dealing with laws that are contrary to the reference and fundamental norms. This non-enforcement has a negative character and cannot be used to repeal the law. In this view, the dominance of the legal aspect of political supervision is not only in conflict with the theory of separation of powers, but also in line with its goals and the rule of law.